Why did Engineering Students Choose to Study in China? 工科学生缘何来华留学 - Zhang, Guoyang; Zhu, Jiabin (Journal of International Students, 2020)
China is currently the third-largest destination country for international students in the world. Among the international students in China, the number of those in engineering schools is increasing most rapidly. Based on the “Push-Pull” theory (Altbach, 1998) and a three-stage decision-making theory (Ma, 2017), this research explored the factors influencing international students’ choices of engineering schools in China. Twenty-two international students in engineering schools at a leading Chinese university were interviewed. Qualitative analyses of the interview data suggested that the participants were attracted to China by the availability of scholarships, ranking of the host university, and opportunities for personal growth and professional development. Meanwhile, it was found that positive relationships between the students’ home countries and China, inadequate educational and research resources in home countries, and higher tuition fees and educational costs involved in studying in Western countries also influenced their decision-making process. 中国已经成为全球第三大留学目的国，其工科留学生数量增速最快、位居所有学科第二。本研究基于囊括宏观因素与微观因素的“推拉”理论和国际学生择校三阶段理论的指导，采用质性研究方法，以S校为研究平台，一对一地访谈了来自亚、欧、美、非洲的22名工科学生,旨在探索形成工科学生来华留学“热潮”的原因。研究发现，可获得的奖学金、雄厚的工科实力、促进个人发展是影响他们来华留学的主要因素，友好的两国关系、母国教育与研究资源的匮乏、西方国家昂贵的留学费用在择校过程中也起到了一定作用。